(untitled) (CIPEEX, 2025)
This open, monocentric clinical trial aimed to evaluate the safety and efficacy of a Picore-Bluecore laser device in the treatment of patients with melasma. Melasma is a common cutaneous hyperpigmentation disorder, whose causes include genetic predisposition, exposure to ultraviolet light, and hormonal changes. Fifteen volunteers, of both sexes, participated in the study and underwent three laser sessions, with intervals of 21 days between them. The sessions used the Zoom handpiece, Blue T mode, with energy of 1.03 mJ/cm² and a pulse of 10 Hz, applied in three passes on the melasma lesions. In addition to laser treatment, participants used daily sunscreen and 4% hydroquinone cream. Clinical evaluation, including photographs and patient self-assessment, indicated a significant improvement in melasma lesions without relevant adverse effects. Tolerability to the treatment was high, with a low level of pain reported by the patients. The results demonstrate that the use of the Picore-Bluecore laser is safe and effective for the treatment of melasma, with a high satisfaction rate among participants. This study reinforces the relevance of picosecond lasers as a minimally invasive and efficient therapeutic option for hyperpigmentation.